Hemorrhagic Fever with Renal Syndrome (History, problems and Research Perspectives) - E. A. Tkachenko; J. K. Dzagurova; A. D. Bernshtein; N. A. Korotina; N. M. Okulova; E. S. Mutnikh; A. P. Ivanov; A. A. Ishmukhametov; Yu. V. Yunicheva; O. M. Pilikova; V. G. Morozov; D. V. Trankvilevskiy; et al. (Эпидемиология и вакцинопрофилактика, 2016)
The work is devoted to clarify the etiological aspects of the hemorrhagic fever with renal syndrome (HFRS), clinical and epidemiological features that are closely linked to the etiology, as well as to development of methods and products for specific diagnosis and vaccine prevention of hantavirus infection. That regard to hantaviruses a set of virological, immunological and molecular-genetics methods were developed significantly enhance the effectiveness of the specific diagnostics of HFRS. The features of humoral immunity in HFRS were identified and atypical clinical forms of HFRS was istablished; indicators of natural immunity to hantavirus in the population living in different regions of Russia and the former Soviet republics have been identified that allowed us to refine nosological area of HFRS; new, previously unknown natural foci of HFRS, including hantavirus RNA, in the central regions of Russia and in the subtropical zone of Krasnodar region have been identified and studied; 76 strains and 70 isolates of 9 rodent species and one species of birds, as well as from the blood of patients with HFRS and sectional materials from HFRS dead patients have been isolated and identified; new hantavirus species - Khabarovsk, Taimyr-Topografov, Adler, as well as two new genotypes Dobrava/Belgrad virus - Kurkino and Sochi have been identified; species composition of small mammals - the natural reservoir of hantaviruses was the refined; etiological role and epidemiological importance of different hantaviruse types in HFRS incidence structure was established; the existence of new etiologically distinct hantavirus infections with significant epidemiological differences has been proven; manufacturing techniques and methods of control of the culture inactivated vaccine against HFRS has been developed.